1985
DOI: 10.1002/1097-0142(19851215)56:12<2881::aid-cncr2820561228>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effectiveness of enteral and parenteral nutrition in reversing or preventing protein-energy malnutrition in advanced neuroblastoma a prospective randomized study

Abstract: The effectiveness of enteral and parenteral nutrition regimens in preventing or reversing protein-energy malnutrition (PEM) and in preventing treatment delays was evaluated in 32 children receiving treatment for newly diagnosed Stage 111 (3 patients) and IV (29 patients) neuroblastoma. Ten of 18 malnourished patients were randomized to central parenteral nutrition (CPN) and 8 to peripheral parenteral nutrition (PPN) plus enteral nutrition for 4 weeks and then received enteral nutrition (EN: intense nutrition c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Furthermore, a poor nutritional status has been associated with an impaired tumour response to treatment and outcome of disease (Donaldson et al, 1981;van Eys, 1982;Rickard et al, 1983a), reduced therapy tolerance van Eys, 1979;Filler et al, 1977;Hays et al, 1983;Rickard et al, 1983aRickard et al, , 1985, impaired immunological function (van Eys, 1979;van Eys et al, 1980) and a reduced state of well-being and performance (Donaldson et al, 1981;van Eys, 1979;Mauer et al, 1990). The aim of nutritional intervention must therefore be the prevention of therapy-related malnutrition and the added effects of protein energy malnutrition (PEM).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a poor nutritional status has been associated with an impaired tumour response to treatment and outcome of disease (Donaldson et al, 1981;van Eys, 1982;Rickard et al, 1983a), reduced therapy tolerance van Eys, 1979;Filler et al, 1977;Hays et al, 1983;Rickard et al, 1983aRickard et al, , 1985, impaired immunological function (van Eys, 1979;van Eys et al, 1980) and a reduced state of well-being and performance (Donaldson et al, 1981;van Eys, 1979;Mauer et al, 1990). The aim of nutritional intervention must therefore be the prevention of therapy-related malnutrition and the added effects of protein energy malnutrition (PEM).…”
Section: Discussionmentioning
confidence: 99%
“…Naso-gastric tube feeding in children with cancer E den Broeder et al Several factors might have contributed to this: (1) The improved availability and ef®cacy of anti-emetics over the past few years has obviously led to better control of the adverse side-effects during courses of chemotherapy; (2) A poor nutritional status of a child with cancer leads to reduced therapy tolerance van Eys, 1979;Filler et al, 1977;Hays et al, 1983;Rickard et al, 1983aRickard et al, , 1985. The nutritional status of the children in the retrospective group was poorer than that in the experimental group at the same point during treatment, which might account for the difference in severity and frequency of vomiting; (3) Protocolized administration of tube feeding leads to optimisation of anti-emetic protocols, as the goal is to be able to administer suf®cient amounts of energy to provide the child's TDER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, three of the Wilms' tumor patients and five children with neuroblastoma had weights or heights below the 10th percentile at the time of diagnosis. The poor prognosis associated wilh nutritional depletion prior to the initiation of chemotherapy has been well documented in previous studies (8,21,22). Rickard and co-workers (21) reported a decreased number of days to tumor relapse or death in children who were malnourished at diagnosis.…”
Section: Discussionmentioning
confidence: 83%
“…The role of conventional diet in maintaining nutritional status during insult A number of studies have shown that conventional feeding with added supplements is insuf®cient in preventing or reversing weight loss in children with leukaemia ± lymphoma (Hays et al, 1983), Wilms' tumours (Rickard et al, 1980), advanced neuroblastoma (Rickard et al, 1985), and a variety of tumours requiring abdominal irradiation (Donaldson et al, 1984). Rickard et al reported a deterioration in the nutritional status of children with Wilm's tumour who did not receive PN compared with those who did (Rickard et al, 1980).…”
Section: Nutritional Intervention Following Bmt: Which Route?mentioning
confidence: 99%